Beliefs related to sexual intimacy, pregnancy and breastfeeding in the public during COVID-19 era: a web-based survey from India - Swapnajeet Sahoo; Jigyansa Ipsita Pattnaik; Aseem Mehra; Ritu Nehra; Susanta Kumar Padhy; Sandeep Grover (Journal of Psychosomatic Obstetrics and Gynecology, 2021)
Aim To evaluate the beliefs held by the public regarding sexual health, pregnancy, and breastfeeding during COVID-19 era. Methods It was an online cross-sectional survey conducted through the Survey Monkey® platform and after proper ethical approval a self-designed questionnaire was circulated by the snowballing sampling technique through the Whatsapp platform. Results 1636 people respondent to the survey questionnaire. 63% of the participants mentioned that kissing could spread nCoV-SARS. Unprotected sexual intercourse with the spouse can cause infection spread, was reported by about one-third (35.9%). Nearly one-fifth (22%) thought that unprotected sexual intercourse with unknown partners/persons could not spread the infection. About half (49.7%) of the participants reported COVID-19 infection can be transmitted from mother to the child/fetus during the process of birth or during pregnancy and one-fifth (21.3%) of the participants reported going ahead with the Cesarean section if the mother is suspected of having or is confirmed to have COVID-19 infection. About one-fifth feared for risk of birth defects and abortion in case the mother is infected with COVID-19. 28% of the participants reported COVID-19 infection can be transmitted to newborn by breastfeeding. Conclusions The present study suggests that a significant proportion of people have misinformation about sexual intimacy, pregnancy, and breastfeeding in the ongoing pandemic which needs to be addressed.